UJI DAYA TERIMA SELAI LABU KUNING (Cucurbita moshata) DAN KANDUNGAN GIZINYA - Ina Sabrina Sitepu; Ernawati Nasution; Etti Sudaryati (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
Pumpkin Jam is one of the innovative processed jams that contain high vitamin C from yellow pumpkin. Pumpkin jam can also be used as a source of daily carbohydrate needs. This research is an experimental research with complete randomized design with two treatment that is A1 with ratio of pumpkin and sugar by 60%: 40%, and A2 with pumpkin and sugar ratio equal to 70%: 30%. Pumpkin jam receipt test conducted on FKM USU students as many as 30 people and nutrient analysis of carbohydrate, fiber and vitamin C was done in Biochemistry Laboratory / KBM FMIPA USU. Based on Mann-Whitney test results, the differences in the treatment of each sample gave a significant effect on the color and texture, but did not affect the aroma and taste of pumpkin jam. The results of organoleptic tests on the color, aroma, taste and texture of pumpkin jam at both treatments included in the likes category. The results of nutrient analysis of pumpkin jam showed that the nutrient content in the pumpkin jars both A1 and A2 treatment each contributed daily nutritional needs of 10% and 9.3% of carbohydrates, Fiber by 5.8% and 17% and vitamins C at 29.2% and 31.3%. It is suggested to the community to be able to utilize the yellow pumpkin as the basic ingredient of making jam and consuming jam of pumpkin as one of the daily energy source.   Keywords: Acceptance  Test, Pumpkin Jam, Yellow Pumpkin, Nutritional Content.